STUDI DAYA DAN KUALITAS HIDUP KALIANDRA MERAH (Calliandra calothyrsus) PADA TIGA JENIS TANAH DI AREAL REKLAMASI BEKAS PENAMBANGAN SEMEN - Akhmad Maulidani; Gusti Muhammad Hatta; Yudi Firmanul Arifin (Jurnal Sylva Scienteae, 2020)
The higher population growth in Indonesia makes the need for cement increase, materials obtained by drilling and blasting. These activities resulted in the opening of areas to mine the material of cement, especially limestone, clay and laterite. This study aims to determine the percentage of survival rate, quality of life and growth of Calliandra calothyrsus  plants in several soil media. The method used by calculating the percentage of survival rate, quality of life and growth of C. calothyrsus plant. The highest percentage of survival of C. calothyrsus  is in lateritic soil area with a percentage of 100% and then in the area of limestone land with a percentage of 94%. The lowest was in the clay soil area with percentage of 79%. The healthiest quality of living of C. calothyrsus  is in limestone soil area with 56% percentage and then the most unhealthy is in laterite soil area with 51% percentage. The most miserable and dead are in the clay land area with a percentage of 6% and 21% respectively. Keywords: Calliandra calothyrsus; limestone; clay; laterite